2021
DOI: 10.1002/cncr.33857
|View full text |Cite
|
Sign up to set email alerts
|

Effects by educational attainment of a mammography screening patient decision aid for women aged 75 years and older

Abstract: BACKGROUND:To help inform screening decisions, a mammography screening decision aid (DA) for women aged 75 years and older was tested in a cluster randomized clinical trial of 546 women. DA use increased women's knowledge of the benefits and harms of mammography and lowered screening rates. In the current study, the objective was to examine whether participants' views of the DA and/or its effects differed by educational attainment. METHODS: A secondary analysis was conducted of 283 women who received the DA be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…14 Also, 84% of patients found the DA helpful regardless of their educational attainment and 97% with a high-school degree or less reported understanding most or all of the DA's information. 31 Notably, these patients are the very patients that PCPs in the current study see. However, the DA was designed for patients to read before a visit and not to support clinician counseling during a visit, which may explain these discrepancies.…”
Section: Varying Views On Acceptabilitymentioning
confidence: 84%
“…14 Also, 84% of patients found the DA helpful regardless of their educational attainment and 97% with a high-school degree or less reported understanding most or all of the DA's information. 31 Notably, these patients are the very patients that PCPs in the current study see. However, the DA was designed for patients to read before a visit and not to support clinician counseling during a visit, which may explain these discrepancies.…”
Section: Varying Views On Acceptabilitymentioning
confidence: 84%
“…Women were enthusiastic about screening based on an interest in taking care of themselves but rely on their providers for health care decisions. Overall, most women found the DA helpful and would recommend the use of the DA Cadet 2021 USA [ 47 ] 283 aged 75–89 Quantitative Secondary analysis Association between women’s educational attainment and their knowledge of the benefits and harms of mammography Decisional conflict, change in screening intention, discussions with PCP and receipt of screening 3 Regardless of educational attainment, 87.2% of the 283 women found the DA helpful. Women with lower educational attainment were less likely to understand all the DA’s content (46.3% vs 67.5%; P < .001), had less knowledge of the benefits and harms of mammography (adjusted mean ± standard error knowledge score, 7.1 ± 0.3 vs 8.1 ± 0.3; P < .001), and were less likely to lower screening intentions (adjusted percentage, 11.4% vs 19.4%; P = .01).…”
Section: Methodsmentioning
confidence: 99%
“…1) [28••]. A tool such as this can help physicians have a productive discussion about ongoing screening and has been demonstrated effective regardless of education level [29].…”
Section: Life Expectancy and Screeningmentioning
confidence: 99%
“…Patients tend to overestimate the benefit of screening studies and are enthusiastic to continue these tests [27,30]. A qualitative study out of NYC found that older women with a long history of screening mammography viewed the test as a necessary and routine part of their care [29,31]. A study of utilizing decision aids in a group of African American women in Philadelphia, most often cited that "getting a mammogram may help me feel good about myself and my health" [32].…”
Section: Patient Perspectives On Screeningmentioning
confidence: 99%
See 1 more Smart Citation